A randomised controlled trial of tidal irrigation vs corticosteroid injection in knee osteoarthritis: the KIVIS Study. - Arden, N; Reading, I; Jordan, K; Thomas, L; Platten, H; Hassan, A; Ledingham, J (2008)
OBJECTIVES: Patients with knee osteoarthritis (OA) often suffer pain that is not fully controlled by analgesics and often require intra-articular therapies. The aim of this study was to compare the benefits of intra-articular corticosteroid injections (CSIs) and tidal irrigation (TI) in patients with OA of the knee. METHODS: We performed a dual-centre, single blind, randomised, parallel group trial comparing TI and CSI. Patients with knee OA were randomised to either irrigation using a 3.2mm arthroscope under local anaesthesia or an intra-articular injection of 40 mg triamcinolone acetonide and 1% lidocaine. Patients were followed for 6 months. The primary outcome measure was the Western Ontario and McMaster Universities OA Index total pain score (visual analogue scale, VAS). RESULTS: One hundred and fifty patients were recruited of whom 71 received TI and 79 CSI. In both treatment groups, over 80% of patients reported improvement at 2 and 4 weeks. After this time, the benefit of CSI decreased whereas that of TI was maintained: at 26 weeks the pain relief afforded by TI was significantly greater than that of CSI. At 26 weeks 29% of the CSI group reported improvement vs 64% of the TI group (P<0.001). Patients with a knee effusion responded better to both treatments, however, this was most apparent for CSI. Patients with less severe radiographic OA also obtained the greatest improvement from both treatments. CONCLUSION: Both procedures lead to significant short-term pain relief of at least 4 weeks, however, TI displayed a significantly greater duration of benefit. Patients with effusions and milder radiographic change obtained the best response to treatment.